O uso de semáforos inteligentes como instrumento no combate à crise de mobilidade urbana: uma análise da cidade de São Paulo - Cavalheiro, Eidy Regina Marcílio (2021)
The Brazilian urbanization process was defined as late, fast paced and uneven. Those characteristics linked with the lack of planning resulted in a series of urban issues among which the so-called mobility crisis. Taking into account, those issues and the current technical-scientific development, innovative technological solutions have been adopted by other metropolises in the world with ways to combat this crisis, an example of those related to smart traffic light control. However, the city of São Paulo, despite having started the use of these technologies in the 1980’s decade, has discontinued its use. Given the known betterment and advancement of this type of technology for urban mobility in cities, as well as its gradual and frequent usage among other metropolises, this study aims to analyze the context of adoption and disuse of smart traffic control technology in the city of São Paulo, and also the feasibility of resuming the use of this type of technology. The methodology used in the study is a qualitative exploratory research, content analysis and the triangulation of information from bibliographic research, systematic literature review, documentary analysis, and interviews with specialists. After due transcription, those interviews were analyzed using the ATLAS.ti software. The results point that lack of continuous and preventive maintenance was one of the key factors leading to the discontinued use of smart traffic lights in the city of São Paulo, in addition to the political-administrative issues and the giganticness of the operation. Furthermore, this research resulted in a series of proposals for the betterment of mobility, specifically regarding the return of traffic lights technologies in the city of São Paulo. These proposals focus mainly on the urban planning sphere, rationalization of land use and occupation, long term strategies for traffic improvement, application of project management concepts in the implementation of traffic light control, and most importantly analyze the best solution for each individual scenario. The results are now expected to contribute to future public policies aimed at solving the urban mobility problems existing in the city of São Paulo.